2015
DOI: 10.1177/0096144215611092
|View full text |Cite
|
Sign up to set email alerts
|

Alone and Far from Home

Abstract: On the basis of nominal data from local foreigners’ files, this article examines gender differences in the trajectories of more than 3,000 single foreign newcomers to Antwerp between 1850 and 1880. The data demonstrate an overall expansion, ruralization, and feminization of the migration field over time, attuned to the evolution of the port town’s dual labor market. Foreign single women were less specialized than their skilled male counterparts and immigrated in large numbers only toward the end of the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…It suggests that women who stayed in Rotterdam were a less favorable selection of the population of origin in terms of health and human capital, and/or that they paid a higher health price for their migration. The former is underlined by a recent study by Hilde Greefs and Anne Winter, in which they showed that women who moved over a longer distance to Antwerp in the latter half of the nineteenth century were—contrary to men—more often from a more modest background (Greefs and Winter 2016). At the same time it is not unthinkable that women—because of their limited human capital—became marginalized upon arrival in Rotterdam.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It suggests that women who stayed in Rotterdam were a less favorable selection of the population of origin in terms of health and human capital, and/or that they paid a higher health price for their migration. The former is underlined by a recent study by Hilde Greefs and Anne Winter, in which they showed that women who moved over a longer distance to Antwerp in the latter half of the nineteenth century were—contrary to men—more often from a more modest background (Greefs and Winter 2016). At the same time it is not unthinkable that women—because of their limited human capital—became marginalized upon arrival in Rotterdam.…”
Section: Resultsmentioning
confidence: 99%
“…This seems to suggest that for migrant women the selection effect was not as strong as it was for men; the difference between migrant women and those who stayed in their region of origin was not as great (cf. Greefs and Winter 2016). Perhaps because of their limited human capital or the lack of a social network, they might have ended up in trouble in the city, which could have prevented them from returning home or moving to another destination.…”
Section: Discussion Policy Implications and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Greefs and Winter, this registration 'appears to have been considered, both by the local authorities and by migrants themselves, a purely administrative procedure inherent to migrants registration in the local population books, which could have been prompted by employers, landlords, neighbours, or simply on initiative of migrants themselves'. 43 However, the local police were unable to consistently detect unregistered foreigners due to a lack of personnel. 44 An unknown number of foreigners was therefore either not registered at all or only months or even years after their arrival.…”
Section: Sources and Methodsmentioning
confidence: 99%